Penerapan Metode Simple Additive Weighting Pada Sistem Pendukung Keputusan Penentuan Siswa Bermasalah Pada SMA Negeri 1 Kabila: Sistem Pendukung Keputusan - Yulanda Yunus; Jorry Karim (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
In this study, a Decision Support System for Determination of Problematic Students Using the Simple Additive Weighting (SAW) Method at SMAN 1 Kabila, the problem that occurs is that the processing of problematic student data is still manual, namely using paper media as storage and data processing that allows the data. can be lost or scattered. The school often finds it difficult to determine students who have problems, because of the many violations of students who often occur. This study aims to help Decision Support Systems as an alternatif solution for data storage and processing that allows data to be lost or scattered. The school requires a decision support system that provides the ability to solve problems precisely, quickly, and accurately to speed up the process of determining problem students. The method used in this research is descriptive method with stages, namely system planning, system analysis, system design, system implementation, system testing using the test case method with white box testing and black box testing approaches. The results of this study indicate that the application of the Decision Support System, it is concluded is appropriate and feasible to use and implement. Based on trials using white box and black box testing, the value of Ciclometic Complexity (CC) = 2 can be concluded that the flowchart logic is correct by using a test case proving that the Decision Support System for Determining Problematic Students Using the Simple Additive Weighting (SAW) Method is more effective and efficient compared to record keeping.